Transposable elements and the detection of somaclonal variation in plant tissue culture - Azman, A.S.; Mhiri, C.,; Grandbastien, M.A.,; Tam, S.M., (Penerbit Universiti Kebangsaan Malaysia, 2014)
Plant tissue culture uses the genetic potential, or totipotency, of plants to regenerate and give rise to a whole plant. Tissue culture-derived plants are expected to have identical genetic material to the parent, and thus can serve as an effective tool for controlled, mass clonal propagation. However, somaclonal variation has been observed in plant tissue culture due to either point mutations, transposition activity of mobile genetic elements, chromosomal rearrangements, or ploidy level changes, causing genetic instability. Tissue culture-induced mutations associated with transposable element activities have been reported from many plant studies, related to stress conditions during tissue culture such as wounding, exposure to hormones and/or specific compounds in the growth media, and genomic shocks from cytological changes. Transposable elements are repetitive DNA fragments with the ability to transpose from one region to another within a genome. Mutations that may occur during plant tissue culture suggest that the plantlets have to be regularly monitored. Methyl-sensitive transposon display (MSTD) is an advanced, efficient DNA fingerprinting technique that can simultaneously detect genetic variation, changes in transposable element insertion sites and the status of cytosine methylation of DNA in plant genomes. The main principles and notes for application of MSTD such as design of element-specific primers, identification of transposable element sequences in plant genomes, selection of the isochizomer enzymes used, and different classes of banding pattern shown are briefly discussed based on our preliminary work with Nicotiana benthamiana (Tnt1 retroelement) and Musa acuminata (Copia-33 Mad-I retroelement) examples.